The Green Consumption Assistant - Gossen , Maike; Jankowski , Patricia (Ökologisches Wirtschaften - Fachzeitschrift, 2022)
E-commerce is here to stay. And it has become very successfulin driving unsustainable behaviors such as overconsumption. How could the same technology be used to guide consumers towards sustainable product choices?